Analysis Of Dog Bites in Kashmir: An Unprovoked Threat to Population - Kouser Sideeq Lone; Sufoora Bilquees; S Mohammad Salim Khan; Inaam Ul Haq (National Journal of Community Medicine, 2014)
Objectives: The study focuses on the analysis of regional distribution, pattern and outcome of dog bite injuries sustained in Kashmiri population and assessing the burden on society.